Giving Legs to Handprint Thinking: Foundations for Evaluating the Good We Do - Guillaume, Joseph H.A.; Sojamo, Suvi; Porkka, Miina; Gerten, Dieter; Jalava, Mika; Lankoski, Leena; Lehikoinen, Elina; Lettenmeier, Michael; Pfister, Stephan; Usva, Kirsi; Wada, Yoshihide; Kummu, Matti (John Wiley & Sons, 2020)
In environmental management and sustainability there is an increasing interest inmeasurement and accounting of benecial impact—as an incentive to action, as a communication tool,and to move toward a positive, constructive approach focused on opportunities rather than problems. Oneapproach uses the metaphor of a “handprint,” complementing the notion of environmental footprints,which have been widely adopted for impact measurement and accounting. We analyze this idea byestablishing core principles of handprint thinking: Handprint encourages actions with positive impacts andconnects to analyses of footprint reductions but adds value to them and addresses the issue of what actionshould be taken. We also identify ve key questions that need to be addressed and decisions that need to bemade in performing a (potentially quantitative) handprint assessment, related to scoping of theimprovement to be made, how it is achieved, and how credit is assigned, taking into account constraints onaction. A case study of the potential water footprint reduction of an average Finn demonstrates howhandprint thinking can be a natural extension of footprint reduction analyses. We  nd that there is adiversity of possible handprint assessments that have the potential to encourage doing good. Their commonfoundation is “handprint thinking.”
Keywords: sustainability; environmental footprints